Functional information technology in geometry-graphic training of engineers - Irina D. Stolbova; Evgeniya P. Aleksandrova; Konstantin G. Nosov (Открытое образование (Москва), 2017)
In the last decade, information technology fundamentally changed the design activity and made significant adjustments to the development of design documentation. Electronic drawings and 3d-models appeared instead of paper drawings and the traditional form of the design documentation. Geometric modeling of 3d-technology has replaced the graphic design technology. Standards on the electronic models are introduced. Electronic prototypes and 3d-printing contribute to the spread of rapid prototyping technologies.In these conditions, the task to find the new learning technology, corresponding to the level of development of information technologies and meeting the requirements of modern design and manufacturing technologies, comes to the fore. The purpose of this paper — the analysis of the information technology capabilities in the formation of geometrical-graphic competences, happening in the base of graphic training of students of technical university. Traditionally, basic graphic training of students in the junior university courses consisted in consecutive studying of the descriptive geometry, engineering and computer graphics. Today, the use of integrative approach is relevant, but the role of computer graphics varies considerably. It is not only an object of study, but also a learning tool, the core base of graphic training of students. Computer graphics is an efficient mechanism for the development of students’ spatial thinking. The role of instrumental training of students to the wide use of CAD-systems increases in the solution of educational problems and in the implementation of project tasks, which corresponds to the modern requirements of the professional work of the designer-constructor.In this paper, the following methods are used: system analysis, synthesis, simulation.General geometric-graphic training model of students of innovation orientation, based on the use of a wide range of computer technology is developed. The implementation of this model is based on the functional characteristics analysis of the applied technology training. We describe the use of a complex system of information technology in various forms of training. This shows the options for the integration of these technologies in the content of the sections of the students’ graphic training, as well as the efficiency of their use.The materials can be used to optimize the learning process in technical universities both in the graphic training and other subject areas.